2020
DOI: 10.1089/neu.2019.6570
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Peripheral Organs following Combined Hypoxemia and Hemorrhagic Shock in a Rat Model of Penetrating Ballistic-Like Brain Injury

Abstract: Polytrauma, with combined traumatic brain injury (TBI) and systemic damage are common among military and civilians. However, the pathophysiology of peripheral organs following polytrauma is poorly understood. Using a rat model of TBI combined with hypoxemia and hemorrhagic shock, we studied the status of peripheral redox systems, liver glycogen content, creatinine clearance, and systemic inflammation. Male Sprague-Dawley rats were subjected to hypoxemia and hemorrhagic shock insults (HH), penetrating ballistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Serum levels of Amyloid A (AA) during 6 to 24 hours posttrauma have been suggested as a prognostic indicator to predict poor outcomes in patients (75,76). Another study showed a positive association between severity of injuries and increased AA concentrations in blood circulation after trauma (77).…”
Section: Saamentioning
confidence: 99%
See 1 more Smart Citation
“…Serum levels of Amyloid A (AA) during 6 to 24 hours posttrauma have been suggested as a prognostic indicator to predict poor outcomes in patients (75,76). Another study showed a positive association between severity of injuries and increased AA concentrations in blood circulation after trauma (77).…”
Section: Saamentioning
confidence: 99%
“…Moreover, an increase in serum concentration of this cytokine at days 4 to 6 after the onset of disease symptoms, which decreases over the next few days, is associated with good prognosis (88). It appears a high expression of IFN-g at admission, which continues for 3 to 4 weeks, could cause negative consequences due to over-activity in the immune (30,32,33,37,80), PCT (30,33,38,(51)(52)(53)55), ferritin (33,68) and SAA (73,75,76,78) system, inducing ACE2 expression (the binding site for SARS-CoV-2) and promoting virus replication (87). Anti-IFN-I autoantibodies have recently been detected in COVID-19 and are associated with poor prognosis of the disease.…”
Section: Ifnsmentioning
confidence: 99%
“…The treatment of CTS in higher concentrations effectively alleviated the above phenomenon. In the preliminary stage of the study, we found that most of the researchers used male animals to build this model [26,27,[34][35][36], thus we speculate that there may be no gender difference in HS-induced liver injury. In addition, there are hormonal changes in the physiological cycle of female rats and mice, thus, in order to avoid the uncontrollable factors, we chose male rats for modeling.…”
Section: Discussionmentioning
confidence: 92%
“…For another, the level of creatinine and urea nitrogen was higher in patients with TBI in plateau areas, and the percentage of renal injury was higher but without significance. Previous studies have demonstrated that multiple systemic and local changes occur following TBI, including liver and renal injury ( 5 , 7 , 17 20 ). Concerning the liver, TBI can modulate the synthesis of acute-phase proteins by hepatocytes and exert the neuro-innate immune response, which further induces acute liver injury with increased expression of oxidative stress markers and mitochondrial dysfunction within hepatocytes ( 5 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that multiple systemic and local changes occur following TBI, including liver and renal injury ( 5 , 7 , 17 20 ). Concerning the liver, TBI can modulate the synthesis of acute-phase proteins by hepatocytes and exert the neuro-innate immune response, which further induces acute liver injury with increased expression of oxidative stress markers and mitochondrial dysfunction within hepatocytes ( 5 , 17 , 18 ). As for the kidney, TBI may cause acute kidney injury through increased sympathetic nervous system activity and plasma catecholamines, systolic hypertension, and hypovolemia by the brain–kidney crosstalk ( 7 , 19 21 ).…”
Section: Discussionmentioning
confidence: 99%